The Effect of Bad Reputation and Increasing Factor Towards Investment Decision: Experimental Study on Young Investor - Purnama, Ida Ayu; Rokhimah, Siti (RSF Conference Series: Business, Management and Social Sciences, 2021)
The purpose of this research is to examine the effectiveness of clawback to increase the intention of young investors in companies that have a bad reputation. This research also examines the intention to invest between independent income groups and non-independent income groups in bad reputation companies. This study uses an experimental method with a 2x2 design between subjects. The subjects of this study amounted to 70 participants. The result showed that there was no difference in the investment interest of young investors, both those who already have income and those who do not have income in bad reputation companies. In addition, clawback could increase the investment interest of young investors to invest in companies that had a bad reputation because of their sense of security